An evaluation of police reporting of road casualties. Issue 1 (3rd February 2009) - Jeffrey, S; Stone, D H; Blamey, A; Clark, D; Cooper, C; Dickson, K; Mackenzie, M; Major, K
Abstract : Background: Under-reporting of road traffic casualties in police records has been well documented. Objectives: To investigate the extent and nature of possible under-reporting of road traffic casualties in the West of Scotland. Design: A linked database comprising both police data (STATS19) and hospital in-patient records (SMR01) was created. The study period was 1997–2005 inclusive. Contrasting the number of SMR01-identified road casualties that were also recorded ("linked") in STATS19 records with those that were not ("unlinked") gives an indication of the extent and types of under-reporting of hospitalized road casualties by the police. Results: 45% of hospital admissions due to road casualties were not reported to (or recorded by) the police. The STATS19 "slight casualties" that were linked to the SMR01 data was the only category that showed an increase in numbers (+4%) over the study period, whereas the numbers of STATS19 KSI (killed or seriously injured—combining fatal and serious casualties) decreased substantially (−38%). Pedal cyclists and motorcyclists were most likely to be missed by police recording. No third-party involvement, older casualties, females, length of stay in hospital (day cases), and earlier year of crash were also significantly associated with under-reporting. Conclusions: A general decline in the completeness of STATS19 is unlikely to have occurred, but there may have been an increasing tendency over time for police officers to report injuries as slight rather than serious. To improve the quality of this information, routine linkage of road casualty data derived from police and hospitalization databases should be considered.